2009
DOI: 10.1007/s10700-009-9067-0
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic-based voting through centered OWA operators

Abstract: Two linguistic-based voting systems have been introduced in recent years, namely: Majority Judgement (Balinski and Laraki in http://ceco.polytechnique.fr/ jugement-majoritaire.html, 2007a) and Range Voting (Smith in http://www.math. temple.edu/~wds/homepage/rangevote.pdf, 2000). The keys for them are aggregation procedures based on the median and the arithmetic mean of the grades assessed to the alternatives, respectively. In this paper a comprehensive framework based on centered OWA operators (Yager in Soft C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 11 publications
(11 reference statements)
0
19
0
4
Order By: Relevance
“…We now introduce a more general notion than that provided by Yager. It was introduced by García-Lapresta and Martínez-Panero [14]. Definition 1.4 Given a weighting vector w of dimension k, the OWA operator associated with w is centered if the following two conditions are satisfied: 1 w k+1−i = w i for every i ∈ {1, .…”
Section: Preliminariesmentioning
confidence: 99%
“…We now introduce a more general notion than that provided by Yager. It was introduced by García-Lapresta and Martínez-Panero [14]. Definition 1.4 Given a weighting vector w of dimension k, the OWA operator associated with w is centered if the following two conditions are satisfied: 1 w k+1−i = w i for every i ∈ {1, .…”
Section: Preliminariesmentioning
confidence: 99%
“…It is worth pointing out that some authors have shown several paradoxes and inconsistencies of MJ (see Felsenthal and Machover [9], Smith [27], García-Lapresta and Martínez-Panero [12] and Nurmi [22], among others).…”
Section: Majority Judgment Extensionsmentioning
confidence: 99%
“…In order to reduce some of the drawbacks produced by MJ in small committees, García-Lapresta and Martínez-Panero [12] developed a proposal in which the linguistic information is aggregated by means of centered OWA operators (Yager [34]), and a 2-tuple fuzzy linguistic representation (Herrera and Martínez [17]). Another way of thinking was proposed by Zahid [37] who combined MJ with the Borda Count [5] in order to avoid some other inconveniences of MJ.…”
Section: Majority Judgment Extensionsmentioning
confidence: 99%
“…Majority Judgment is a controversial method and some authors have shown several paradoxes and inconsistences (see Smith [22], Felsenthal and Machover [9], García-Lapresta and Martínez-Panero [12] and Nurmi [17], among others).…”
mentioning
confidence: 99%
“…For instance, García-Lapresta and Martínez-Panero [12] proposed an extension for small committees where the linguistic information is aggregated by means of centered OWA operators (Yager [28]) and the 2-tuple fuzzy linguistic representation (Herrera and Martínez [14]). In Falcó and García-Lapresta [7,8], an extension based on the distances between linguistic terms is introduced.…”
mentioning
confidence: 99%